Occupational skin cancer due to UV-irradiation: analyses of notified cases as “virtually-certain” occupational disease in Germany between 2005 and 2011 - Schmitt, Jochen Maximilian; Diepgen, Thomas L. (Journal der Deutschen Dermatologischen Gesellschaft, 2014)
Background UV-induced skin cancer is not yet included in the German ordinance on occupational diseases and can only be notified and recognized acknowledged as “virtually-certain” occupational disease. The objective of the study was to analyze notified and acknowledged cases of occupational skin cancer due to UV-irradiation in Germany between 2005 and 2011. Patients and Methods All notified cases of occupational skin cancer due to UV-irradiation have been analyzed which have been registered by the German Statutory accident insurance as of May 2012 were analyzed. The data analyze was descriptive stratified annually for presenting time trends.Data analysis was descriptive, stratified by year to defect time trends. Results Notified cases have increased annually with a total of 548 registered cases of occupational skin cancer induced by UV-irradiation between 2005 and 2011, and 74 recognized acknowledged cases. In 56 cases the procedure was not yet finished. Squamous cell carcinoma (SCC) and in-situ squamous cell carcinoma (actinic keratosis, Bowen's disease) were most frequent and have been the most frequentlyobserved in 333 notified cases. and between 15.6 % and 24.9 % have been recognizedof cases with SCC and actinic keratosis were recognized, respectively. 184 patients with basal cell carcinoma were notified but only 6.5 % recognized acknowledged and only 3 cases with exclusive basal cell carcinoma. Out of 50 notified patients with Mmelanoma only one was recognizedacknowledged. Conclusions The results are in good agreement with the proposal of the German Minister of labor to establish UV-induced skin cancer as a new occupational disease.